2019
DOI: 10.1080/09645292.2019.1680955
|View full text |Cite
|
Sign up to set email alerts
|

Education as investment, consumption or adapting to social norm: implications for educational mismatch among graduates

Abstract: Relying on data for Belgian graduates, we investigate the relationship between motives to participate in higher education (investment, educational consumption, student life consumption and social norms) and overeducation after graduation. We also examine whether these motives affect the relationship between overeducation and other outcomes like wages and job satisfaction. Key findings are that individuals motivated by educational consumption are less likely to be overeducated but face a stronger job satisfacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 46 publications
1
15
0
Order By: Relevance
“…A total of 14 articles were identified as showing the very dominant role that the cost factor of education has in influencing parents' awareness in decision-making on investing in education [2,31,[33][34][35][36][37][39][40][41][42][44][45][46]. Two factors primarily affect the cost of education and can affect parents' awareness when investing in education: out-of-pocket expenses (14 articles) and forgone earnings (three articles).…”
Section: Factor 1: Education Costsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 14 articles were identified as showing the very dominant role that the cost factor of education has in influencing parents' awareness in decision-making on investing in education [2,31,[33][34][35][36][37][39][40][41][42][44][45][46]. Two factors primarily affect the cost of education and can affect parents' awareness when investing in education: out-of-pocket expenses (14 articles) and forgone earnings (three articles).…”
Section: Factor 1: Education Costsmentioning
confidence: 99%
“…The introductory study found that previous researchers had defined the cost of education through two factors. Firstly, the cost of education is seen only in terms of the total direct expenditure used to fund education [2,31,[33][34][35][36][37][39][40][41][42][44][45][46]. Secondly, the cost of education is not only seen as costs directly incurred but also as lost opportunities in earning income as a result of not taking education and entering the labour market [2,40,45].…”
Section: Factor 1: Education Costsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sellami et al (2015), looking at the determinants of student choices in higher education majors found, using longitudinal data from Flanders, that students who choose their field of study because they are interested in the field of study in itself and enjoy studying, have better labour market outcomes than those who choose for other reasons.19 The literature is strongly focused on secondary education with 44 studies providing comment on career-focused mediated provision received by pupils between the ages of 12 and 19. Looking at specific interventions, four areas have been investigated by five or more studies: leadership, mentoring, career guidance, and work-related learning.20 GCSE is a qualification in a specific subject typically taken by school students aged 14-16, at a level below A Level in the United Kingdom (except Scotland).…”
mentioning
confidence: 99%
“…Vertical underemployment can have an impact on individuals in terms of well‐being. Evidence has found that overeducation leads to higher dissatisfaction with both jobs and life compared with those who are not overeducated (Sellami, Verhaest, Nonneman and Trier, 2019). Vertical underemployment also has an impact upon earnings: individuals who were overeducated in fields that were not related to their studies were subjected to three times the penalty to those whose degrees were related to their field (Li, Malvin and Simonson, 2014).…”
Section: Over‐educated Over‐qualified and Underemployedmentioning
confidence: 99%